MENGGALI DAN MENGEMBANGKAN POTENSI DAERAH DALAM PERWUJUDAN OTONOMI DAERAH â€œPerspektif Konseptualâ€ - MN, Nuryasman (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2008)
The implementation of the territory autonomy has been for more than 8 years, but until today, it cannot give any added value to the territories yet. In fact most territories do not know what they sholud do in managing their territory such as how to do administration and how to develop sources of economic potentials. Until now, most territories still use funds from Central Government to finance their activities. Although there is a regulation stating that local governments must use funds from their local potentials and the funds from the Central Government are just a support. The objective of this paper is to help for local government dicover the local economic potentials. For that purpose, there are some methods or theories that can be used: (1) comparative advantage theori; (2) economic based theory; (3) shift share analysis; (4) input output analysis. The use of every methods determined by the availability of data sources and local gevernment capability to develop their territory.